A Jigsaw Puzzle Layer Cake of Spatial Data. Issue 19 (13th May 2014) - Ma, Xiaogang; Fox, Peter
<x xml:space="preserve">Abstract</x> The Infrastructure for Spatial Information in Europe (INSPIRE; http://inspire.jrc.ec.europa.eu) is a European Union (EU) directive that aims to provide a legal framework to share environmental spatial data among public sector organizations across Europe and to facilitate public access to data. To meet these goals, INSPIRE's organization is analogous to a layer cake in which each layer is composed of interlocking pieces of a jigsaw puzzle. The metaphor, although mixed, is apt (see additional supporting information in the online version of this article), and as researchers outside the program, we offer our perspective on how INSPIRE may address challenges raised by the variety of data themes and the wide coverage of collaborators.